(untitled) (Journal of Mechanical Engineering, 2009)
The present demand of energy is increasing day by day due to various reasons such as increasing population, the aspiration for improved living standards and general economic and industrial growth. In the wake of the increasing world energy crisis, which mostly affected the least developed countries, the interest in alternative energy resources has been increased considerably. In this regard, wind as a source of energy can hold good prospect for a underdeveloped country like Bangladesh. Besides, utilization of wind energy has been growing rapidly in the whole world due to environmental pollution, consumption of the limited fossil fuels and global warming. Bangladesh has fairly wind energy potential, exploitation of the wind energy is still in the crawling level. In the current study, wind characteristics and wind energy potential of Teknaf, Kutubdia, Sandwip, Kuakata, and Mongla in the Coastal Areas are investigated. The measured wind data were processed as hourly and monthly basis. Weibull probability density functions of the locations are calculated in the light of observed data and Weibull shape parameter and scale parameter are also calculated. The main objective is to find out wind energy potential for the utilization. Keywords: Wind energy, Weibull distribution, Wind power, Coastal area. doi:10.3329/jme.v39i1.1833 Journal of Mechanical Engineering, vol. ME39, No. 1, June 2008 45-49